miR-200a as Potential Early-onset Biomarker, while High Nitric Oxide as Potential Late-onset Biomarker in Preeclampsia - Hudila Rifa Karmia; Yusrawati Yusrawati; Jamsari Jamsari; Hardisman Hardisman (The Prodia Education and Research Institute (PERI), 2025)
BACKGROUND: miR-200a is known to alter trophoblast invasion and spiral artery remodeling, leading to defective placentation that causes placental hypoxia, which is the main pathomechanism in early-onset preeclampsia (EOPE). Hypoxic placentas cause systemic endothelial dysfunction that is characterized by low production of endothelial vasodilator, mainly nitric oxide (NO). On the other hand, defective placentation does not cause late-onset preeclampsia (LOPE), making the role of miR-200a expression and NO level as predictors in LOPE questionable. Therefore, this study was conducted to compare miR-200a expressions and NO levels in EOPE and LOPE to clarify their role in pathomechanism of both types of preeclampsia.METHODS: A cross-sectional comparative study was conducted in 62 preeclamptic patients (31 EOPEs and 31 LOPEs). Subjects were classified into EOPE or LOPE groups based on whether the diagnosis of preeclampsia was made at <34 or ≥34 weeks of pregnancy. miR-200a expression was analyzed using real-time polymerase chain reaction technique, and NO level was analyzed using colorimetric assay method.RESULTS: EOPE and LOPE subjects were equivalent in terms of age and parity (p=0.709 and p=0.066), but significantly difference in gestational age (p=0.000). miR-200a were expressed in 74.2% of EOPE and 41.9% of LOPE subjects (p=0.010). Median NO levels were lower in EOPE compared to LOPE subjects (23.75 vs. 106.00 µmol/L) (p=0.027), and lower in subjects with detected miR-200a compared to subjects with undetected miR-200a (62.75 vs. 132.25 µmol/L) (p=0.032).CONCLUSION: miR-200a was more expressed in EOPE compared to LOPE subjects suggesting that it might be a significant in predicting EOPE. While NO level was significantly lower in EOPE whilst higher in LOPE subjects, hence might be potential as a marker to differentiate EOPE and LOPE.KEYWORDS: miR-200a expression, NO level, early-onset preeclampsia, late-onset preeclampsia